Analisis Proses Kognitif Siswa Dalam Pemecahan Masalah Berdasarkan Taksonomi Bloom Revisi - Napu, Timotius Woda (Jurnal Ilmiah Mandala Education (JIME), 2021)
The purpose of this research was to determine the cognitive processes that occur in problem solving for Class VIII A students of SMPK St. Paulus Karuni. Type of this research is a qualitative descriptive research, by analyzing the results of students based on Bloom's Revised Taxonomy. The subjects of this research were students of VIII A SMPK St. Paulus Karuni in the 2018/2019 academic year consisting of 11 students, which is a special class that uses a metacognitive and discursive approach to mathematics learning. Collecting data in this qualitative descriptive research is in the form of test results from students. As supporting data in this research, students are given special rules in carrying out tests. Namely students may only make scratches in addition to the answers given. Based on the results and discussion of students of class VIII A SMPK St. Paulus Karuni consisting of 11 students, there are four different types of answers. The results of the cognitive process analysis are 9 students with the first and fourth types of answers able to reach the C5 level or meet the first five indicators. One student with the second type of answer is able to reach the C4 level or meet the first 4 indicators. Whereas one other student who has the third type of answer, is able to reach level C2 or only meet the first two indicators